Fruit and vegetable biowaste as a source of functional nutritional components for animal feed - Tedesco, Doriana E. A.; Guerrini, Alessandro; Giovanelli, Gabriella (Frontiers in Sustainable Food Systems, 2025)
The recovery of fruit and vegetable waste (FVW) from markets and processing plants should be considered a resource for functional feed ingredients since these wastes are rich in nutrients and valuable bioactive compounds. This study focused on FVW from the wholesale market in Milan, which is the largest in Italy, to evaluate the dietary fiber (DF), insoluble dietary fiber (IDF), soluble dietary fiber (SDF), total polyphenol content (TPC), and antioxidant activity (AA) of the FVW collected monthly over the course of a year. Compositional parameters were evaluated based on the month and season of collection (winter, spring, summer, and autumn). The samples collected each month were representative of the month and seasonality of harvesting and commercialization. The DF, IDF, SDF, TPC, and AA were statistically different (p < 0.05) based on the month and season, except for the TPC. Considering the seasonal pattern, the DF content was higher in the autumn and winter seasons (33.3 g/100 g dw and 30.8 g/100 g dw) than in the spring and summer seasons (19.9 g/100 g dw and 21.9 g/100 g dw). A similar trend was observed for the IDF content, which was higher in autumn and winter compared to spring and summer. The SDF content was higher in the summer (9.1 g/100 g dw) and autumn samples (8.1 g/100 g dw). The TPC was similar across the samples collected in different months (overall mean 2.4 ± 0.8 g/100 g dw), without significant differences based on the season of waste generation. The AA content was higher in the spring samples, albeit with high variability (34.4 ± 22.4 μmol TE/g dw). The overall mean solid content in the FVW samples was 10.8 ± 1.2 g/100 g. The results showed that FVW is a valuable source of functional compounds, which may improve the nutritional quality of animal feed. The major constraints in using FVW are the variability in the components from month to month, the presence of anti-nutritional components, and the water content, which compromises product stability. Future investigations are necessary for the recovery of this waste, given its potential added value as a functional feed ingredient.